Специфическая структурно-логическая модель управления чрезвычайной ситуацией - Avramenko, Oleksandr; Ilchenko, Mykola; Lysychenko, Kostiantyn; Farrakhov, Oleksandr; Mirnenko, Volodymir; Shevchenko, Olga (Social development & security, 2020)
161